The Multi‐Functional Use of Large Tree Cavities by Arboreal Vertebrates in a Temperate Broadleaved Forest of Eastern Europe - Yehor Yatsiuk (Ecology and Evolution)
ABSTRACT Tree cavities offer protected shelters and resources for arboreal vertebrates worldwide. In general, cavities with larger openings are better accessible for predators and are avoided by smaller species for breeding, but can still be attractive for occasional use. The current study explores the diversity of functional use types and species interactions at the largest available tree cavities (entrance width ≥ 10 cm) in a temperate European forest with a low number of large cavity‐breeding species. Year‐round camera observations at 9 cavities (range 0.7–3.5 years) revealed 34 visiting species of birds and mammals, including non‐cavity‐breeding species. The top predator threatening other large‐cavity users was European pine marten (Martes martes), which regularly visited each cavity year‐round, on average every 0.7 months. Tawny owl (Strix aluco) was the only species successfully breeding in cavities, arguably because of its ability to defend the nests. However, other species visited cavities at an average rate of 1.5 visits per day, making predominantly short visits (less than 30 s) interpreted as exploration, searching for food, or inspecting for the presence of owls (mobbing). Making short visits and time segregation with predators was a behavioural strategy to exploit cavities for most species. These results confirm that, similarly to other keystone structures (large arboreal nests, ground burrows, etc.), large tree cavities attract a significant part of the arboreal vertebrate community and enrich their habitats. To sustain these functions in wooded ecosystems, management should provide a surplus of available cavities and diversity of their characteristics even when the apparent number of breeding species is low.